Molecular Gating of an Engineered Enzyme Captured in Real Time - Kokkonen, Piia; Sykora, Jan; Prokop, Zbynek; Ghose, Avisek; Bednar, David; Amaro, Mariana; Beerens, Koen; Bidmanova, Sarka; Slanska, Michaela; Brezovsky, Jan; Damborsky, Jiri; Hof, Martin (Journal of the American Chemical Society, 2018)
Enzyme engineering tends to focus on the design of active sites for the chemical steps, while the physical steps of the catalytic cycle are often overlooked. Tight binding of a substrate in an active site is beneficial for the chemical steps, whereas good accessibility benefits substrate binding and product release. Many enzymes control the accessibility of their active sites by molecular gates. Here we analyzed the dynamics of a molecular gate artificially introduced into an access tunnel of the most efficient haloalkane dehalogenase using pre-steady-state kinetics, single-molecule fluorescence spectroscopy, and molecular dynamics. Photoinduced electron-transfer-fluorescence correlation spectroscopy (PET-FCS) has enabled real-time observation of molecular gating at the single-molecule level with rate constants ( kon = 1822 s-1, koff = 60 s-1) corresponding well with those from the pre-steady-state kinetics ( k-1 = 1100 s-1, k1 = 20 s-1). The PET-FCS technique is used here to study the conformational dynamics in a soluble enzyme, thus demonstrating an additional application for this method. Engineering dynamical molecular gates represents a widely applicable strategy for designing efficient biocatalysts.
Keywords: Catalytic Domain; biokatalýza; Biocatalysis; Molecular Dynamics Simulation; kinetika; simulace molekulární dynamiky; mutace; proteinové inženýrství; Hydrolases; Mutation; Protein Conformation; Kinetics; Protein Engineering; konformace proteinů; Sphingomonadaceae; katalytická doména; hydrolasy